Association of prenatal exposure to acetaminophen and coffee with childhood asthma. Issue 2 (16th December 2015) - Liu, Xiaoqin; Liew, Zeyan; Olsen, Jørn; Pedersen, Lars Henning; Bech, Bodil Hammer; Agerbo, Esben; Yuan, Wei; Li, Jiong
Abstract: Purpose: Some studies have suggested that maternal acetaminophen use during pregnancy is associated with asthma in the offspring, and coffee consumption may modify the toxicity of acetaminophen. We aim to examine whether pregnancy maternal acetaminophen use increases the risk for offspring asthma, and whether such a potential association could be modified by maternal coffee consumption. Methods: We included 63 652 live‐born singletons enrolled in the Danish National Birth Cohort. Maternal acetaminophen use and coffee consumption during pregnancy were assessed prospectively via the enrolment questionnaire and three computer‐assisted telephone interviews. Asthma cases were identified by using the Danish National Patient Register and the Danish National Prescription Registry. We estimated the hazard ratios (HRs) for asthma according to prenatal acetaminophen and coffee exposure using Cox proportional hazards regression model. Results: After adjusting for potential confounders, acetaminophen use during pregnancy was associated with an increased risk of offspring asthma (HR = 1.16, 95% confidence interval (CI): 1.11–1.22). Coffee drinking during pregnancy was associated with a slightly decreased risk (HR = 0.94, 95%CI: 0.90–0.99). But there was no strong evidence of effect measure modification of acetaminophen use on offspring asthma by coffee consumption. Conclusions: Acetaminophen use during pregnancy was associated with a modest increased risk for offspring asthma, which was not modified by coffee consumption. Copyright © 2015 John Wiley & Sons, Ltd.